Alexithymia and Inflammatory Bowel Disease: A Systematic Review - Martino, Gabriella; Caputo, Andrea; Schwarz, Peter; Bellone, Federica; Fries, Walter; Quattropani, M. C.; Vicario, C. M. (Frontiers in Psychology, 2020)
Background: Given the role of alexithymia—as the inability to identify, differentiate, and express emotions—in chronic and immune-mediated illness, this systematic review analyzed the prevalence of alexithymia in patients with inflammatory bowel diseases (IBDs), mainly represented by Crohn's disease (CD) and ulcerative colitis (UC). Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed throughout this systematic review of the literature published between 2015 and 2020 in indexed sources from PubMed, PsycINFO, Scopus, and Web of Science databases. Search terms for eligible studies were: “Inflammatory bowel disease” AND “Alexithymia” [Titles, Abstract, Keywords]. Inclusion criteria were: articles written and published in English from 2015 and up to April 2020, reporting relevant and empirical data on alexithymia and IBD. Results: The initial search identified 34 indexed scientific publications. After screening, we found that five publications met the established scientific inclusion criteria. Overall, the mean value of alexithymia ranged from 39 to 53.2 [Toronto Alexithymia Scale (TAS-20) score], thus mostly falling in non-clinical range for alexithymia (≤51). Comparisons of alexithymia between patients with UC and CD highlighted that patients with CD showed externally oriented thinking and difficulties identifying feelings to a greater extent. Regarding comparisons with other samples or pathologies, patients with IBD were more alexithymic than healthy controls and less alexithymic than patients with major depressive disorder, but no difference was found when compared with patients with irritable bowel syndrome (IBS). Then, regarding correlations with other variables, alexithymia was positively associated with anxiety and depression, as well as with psychopathological symptoms and somatic complaints. Conclusion: This systematic review suggests that patients with IBD cannot be generally considered alexithymic at a clinically relevant extent. However, their greater alexithymic levels and its associations with psychological variables and somatic distress may suggest a reactivity hypothesis, in which living with IBD may progressively lead to impaired emotion recognition over time. Specifically, the relationship between IBD and IBS should be further explored, paying deeper attention to the clinical psychological functioning of CD, as IBD requires more emotional challenges to patients.